Hyperpolarization-Activated Cyclic Nucleotide-Gated Channels: An Emerging Role in Neurodegenerative Diseases - Chang, Xiaoli; Wang, Jun; Jiang, Hong; Shi, Limin; Xie, Junxia (Frontiers in Molecular Neuroscience, 2019)
Neurodegenerative diseases such as Parkinson’s disease (PD), Alzheimer’s disease (AD), amyotrophic lateral sclerosis (ALS) and spinal muscular atrophy (SMA) are chronic, progressive and age-associated neurological disorders characterized by neuronal deterioration in specific brain regions. Although the specific pathological mechanisms underlying these disorders have remained elusive, ion channel dysfunction has become increasingly accepted as a potential mechanism for neurodegenerative diseases. Hyperpolarization-activated cyclic nucleotide-gated (HCN) channels are encoded by the HCN1-4 gene family and conduct the hyperpolarization-activated current (Ih). These channels play important roles in modulating cellular excitability, rhythmic activity, dendritic integration and synaptic transmission. In the present review we first provide a comprehensive picture of the role of HCN channels in PD by summarizing their role in the regulation of neuronal activity in PD-related brain regions. Dysfunction of Ih may participate in 1-methyl-4-phenylpyridinium (MPP+)-induced toxicity and represent a pathogenic mechanism in PD. Given current reports that the critical role of HCN channels in neuroinflammation and depression, we also discussed the putative contribution of HCN channels in inflammatory processes and non-motor symptoms in PD. In the second section, we summarize how HCN channels regulate the formation of β-amyloid peptide in AD and the role of these channels in learning and memory. Finally, we briefly discuss the effects of HCN channels in ALS and SMA based on existing discoveries.